Modeling and analysis of three-phase boost rectifier for DC fast EV charging - Srivichai, Jeerapong; Somsai, Kittaya; Pornsuwancharoen, Nithiroth (Institute of Advanced Engineering and Science, 2025)
This research investigates the modeling and analysis of a three-phase boost rectifier for DC fast charging systems for electric vehicles (EVs). A mathematical model validated with MATLAB/Simulink simulations examines system behavior under various conditions. Performance analysis in the abc and dq coordinate systems reveals high consistency with theoretical calculations. The average voltage in the dq frame was found to be vd was 685 V and vq was 0 V, with a discrepancy of less than 0.1% from calculated values. However, the average current in the dq frame showed discrepancies due to cross-coupling effects and circuit impedance. Simulations reported id was 211.50 A and iq was 93.50 A, compared to calculated values of id was 151.97 A and iq was 0 V. For the output DC voltage and current, the average values were 983.05 V and 98.31 A, respectively. Three test cases were analyzed, consist of unbalanced three-phase conditions, voltage drops, and load step responses. Case 1 showed the highest total harmonic distortion (THD), Case 2 increased THD further, and Case 3 achieved the lowest THD, demonstrating improved stability under dynamic loads. These findings confirm the system’s minimal deviations from theoretical predictions, enhanced voltage quality, harmonic mitigation, and improved charging efficiency for EV fast charging applications.